Optimization and Investigation of a Free-Piston Stirling Engine based on Power and Frequency using Genetic Algorithm - Pongnarin Savangvong; Banterng Silpsakoolsook; Sutapat Kwankaomeng (My University, 2019)
This paper presents optimum design and performance investigation of a Free-Piston Stirling Engine (FPSE) by using genetic algorithm (GA). Mechanical and thermal analyses were considered in the optimization. Power and frequency were chosen primarily as the output performance. The mathematical model of the FPSE was provided from equation of motion in state space. The required engine operation frequency was set. The root of equation of motion is function of five unknowns including piston mass, displacer mass, stiffness of piston, stiffness of displacer and damping due to load. The engine operation with desired frequency occurs when two roots of equation of motion are imaginary part, which indicates operation frequency of the engine and other two roots are negative real part. The difference of operation frequency from equation of motion and desired frequency was set as the first objective function. The damping due to load which represents the work output of the engine was set as second objective function. Both objective functions were solved by GA.
Keywords: Piston (optics); Advanced Thermodynamic Systems and Engines